Stock price prediction - Das, Kaushik; Azad, Tahzib; Islam, Sadid; Chowdhury, Nuzhat; Ahmed, Nazia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.